2014
DOI: 10.4103/2278-330x.126518
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nutritional status of gynecological cancer cases in India and comparison of subjective and objective nutrition assessment parameters

Abstract: Aim:To assess the nutritional status of gynecological cancer patients using scored Patient Generated Subjective Global Assessment (PG-SGA) then compare it with the body mass index (BMI), hemoglobin, serum albumin, and approximate percentage weight lost in last 1 month so as to find any one parameter that can be used in place of the comprehensive assessment tool.Materials and Methods:Sixty gynecological cancer patients were assessed for their nutritional status using BMI, serum albumin, hemoglobin, percentage w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 23 publications
1
16
0
6
Order By: Relevance
“…However, Laky et al 13 found that women with ovarian cancer were more susceptible to NS alterations, while patients with endometrial and uterine cancer comprise a group that is less predisposed to such alterations, which parallels our findings. More recently, Das et al 14 Indeed, the rate of malnutrition in cancer patients seems to depend not only on tumor location, but on histological type, staging and cancer treatment. [15][16][17][18] By analyzing the effect cancer site and stage has on NS, we found no significant difference, that is, NS shared the same distribution pattern across different sites and stages of cancer.…”
Section: Discussionmentioning
confidence: 98%
“…However, Laky et al 13 found that women with ovarian cancer were more susceptible to NS alterations, while patients with endometrial and uterine cancer comprise a group that is less predisposed to such alterations, which parallels our findings. More recently, Das et al 14 Indeed, the rate of malnutrition in cancer patients seems to depend not only on tumor location, but on histological type, staging and cancer treatment. [15][16][17][18] By analyzing the effect cancer site and stage has on NS, we found no significant difference, that is, NS shared the same distribution pattern across different sites and stages of cancer.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, despite of the low frequency of underweight individuals diagnosed by the BMI, roughly 33% of the patients had cachexia and/or weight loss greater than 5% before chemoradiotherapy. Other authors also reported a pre‐treatment weight loss ranging from 26% to 40% among patients with gynaecological cancer . Weight loss and anorexia, present in cancer cachexia, can provoke a limitation in the doses of chemoradiotherapy, in addition to higher chances of treatment toxicity .…”
Section: Discussionmentioning
confidence: 99%
“…Other authors also reported a pre-treatment weight loss ranging from 26% to 40% among patients with gynaecological cancer. 34,35 Weight loss and anorexia, present in cancer cachexia, can provoke a limitation in the doses of chemoradiotherapy, in addition to higher chances of treatment toxicity. 15 It has been suggested that the %WL seems to be a better parameter than BMI in cancer patients undergoing chemotherapy 36 and a good prognostic factor of QoL irrespective of the type of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…First of all, weight loss does not totally represent malnutrition status. Other reported methods for the evaluation include descending change in serum albumin and hemoglobin level during treatment, as well as the scored Patient Generated Subjective Global Assessment (PG-SGA) (Das et al 2014). Nevertheless, weight loss is closely related to those parameters, and our data provided an essential clue for further research.…”
Section: Discussionmentioning
confidence: 99%